Efficacy of a novel augmentative and alternative communication system in promoting requesting skills in young children with Autism Spectrum Disorder in India: A pilot study. (August 2022) - Srinivasan, Sudha; Patel, Siddhi; Khade, Avadhut; Bedi, Gaganjot; Mohite, Jyoti; Sen, Ajanta; Poovaiah, Ravi
Background & aims: The study assessed the efficacy of a novel, child-friendly, socio-culturally sensitive, icon-based Augmentative and Alternative Communication (AAC) system called Jellow Communicator, in teaching requesting skills to young children with Autism Spectrum Disorder (ASD) in a special school in Mumbai, India. Jellow is a comprehensive AAC system with a lexicon and pictorial library designed using a participatory, user-centric design process. The content of Jellow has been developed bearing in mind the socio-cultural and linguistic diversity of India. Jellow is available in low-tech (flashcards, booklet) and high-tech (Android and iOS app and desktop application) versions.Methods: The quasi-experimental longitudinal study involved seventeen 3.5–12-year-old children with ASD with communication challenges. Children were taught to use the Jellow AAC system to request for preferred items, as part of their regular speech therapy sessions. Each child received one-on-one training sessions with a licensed speech therapist twice a week over a 3-month duration, with each session lasting around 20–30 min. A systematic training protocol adapted from the original Picture Exchange Communication System (PECS) was developed to train children to use the Jellow system, progressing from flashcards to the app version of Jellow. Behavioral training strategies such as modeling, least-to-most prompting, differential reinforcement, and behavior chain interruption were used to facilitate requesting behaviors. The speech therapist assessed children's developmental level across multiple domains at pretest and posttest. We coded 3 videos per child, i.e., one early, one mid, and one late training session each, to assess changes in children's stage of communication, spontaneous requesting abilities, level of attention during training trials, and average time to completion for requesting trials. In addition, caregivers filled out questionnaires to assess training-related changes in children's adaptive functioning levels as well as the psychosocial impact of the Jellow AAC system on children's quality of life.Results: Children significantly improved their stage of communication, and a majority of children transitioned from flashcards to using the Jellow app to request for preferred items. Children also increased the proportion of spontaneous requests over the course of training. Caregivers reported a positive perceived psychosocial impact of the Jellow AAC system on their child's self-esteem, adaptability, and competence.Conclusions: The findings from our pilot study support the use of the novel, socio-culturally adapted, Jellow Communicator AAC system for teaching requesting skills to young children with ASD who use multiple communication modalities. Future studies should replicate our findings with a larger group of participants using a randomized controlled trial design.Implications: This is the first experimental study to systematically assess the effects of an indigenously-developed comprehensive AAC system adapted to the sociocultural and linguistic landscape of India. Our study results provide support for the use of the cost-effective Jellow Communicator AAC system in facilitating requesting skills in children with ASD who use multiple communication modalities. Clinicians can use low-tech and high-tech versions of Jellow to promote communication skills in children with ASD.